2017
DOI: 10.3390/catal7050151
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Citric Acid on MoO3/Al2O3 Catalysts for Sulfur-Resistant Methanation

Abstract: A series of MoO 3 /Al 2 O 3 catalysts with different amounts (molar ratio of CA/Mo = 0, 1, 1.5, and 2) of citric acid (CA) prepared by simultaneous impregnation were evaluated for sulfur-resistant methanation. Based on the evaluation results, catalytic activity increased accompanied with the rise of citric acid amount. Combine with the analysis of N 2 -physisorption, XRD, H 2 -TPR, XPS, and TEM, the catalyst saturated loading capacity improved, resulting in increasing dispersion of Mo species on Al 2 O 3 surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 29 publications
(29 reference statements)
1
4
0
Order By: Relevance
“…Reduction of pure MoO 3 occurs at 767 (corresponding to MoO 3 → MoO 2 ) and 997 °C (MoO 2 → Mo). A minor shoulder to the first peak at 797 °C (corresponding to Mo 4 O 11 formed by the reduction of MoO 3 ) was also reported. , In the case of Mo/ZrO 2 , the two reduction peaks observed at 400–420 and 800–940 °C were assigned to octahedral and tetrahedral molybdenum oxide species, respectively. , In the present study, (for 4Pt-8MoO x /Al 2 O 3 ) the reduction peak of octahedral molybdenum oxide had shifted to 173 °C because of its intimate contact with platinum. Zhu et al reported a low-temperature reduction peak at 320 °C and a high-temperature peak above 800 °C for Pt-5WO x /Al2O 3 , attributable to reduction of WO 3 to WO 2.9 and WO 2 , respectively.…”
Section: Resultssupporting
confidence: 77%
“…Reduction of pure MoO 3 occurs at 767 (corresponding to MoO 3 → MoO 2 ) and 997 °C (MoO 2 → Mo). A minor shoulder to the first peak at 797 °C (corresponding to Mo 4 O 11 formed by the reduction of MoO 3 ) was also reported. , In the case of Mo/ZrO 2 , the two reduction peaks observed at 400–420 and 800–940 °C were assigned to octahedral and tetrahedral molybdenum oxide species, respectively. , In the present study, (for 4Pt-8MoO x /Al 2 O 3 ) the reduction peak of octahedral molybdenum oxide had shifted to 173 °C because of its intimate contact with platinum. Zhu et al reported a low-temperature reduction peak at 320 °C and a high-temperature peak above 800 °C for Pt-5WO x /Al2O 3 , attributable to reduction of WO 3 to WO 2.9 and WO 2 , respectively.…”
Section: Resultssupporting
confidence: 77%
“…The X-ray Diffraction (XRD) patterns of Mo-Al and Pd/Mo-Al catalysts with various palladium contents (1-4 wt%) are shown in Figure 1A, and Figure 1B shows the enlarged view XRD pattern of Mo-Al catalyst. For all catalysts, the diffraction peaks of γ-Al2O3 were identified at 2θ = 45.8° and 67.1° [29] while the peaks at 2θ = 23.4° and 25.7° were assigned to the crystalline MoO3 phase [30]. In addition, other peaks at 2θ = 20.7°, 22.0°, 23.4°, and 25.7° were identified, which are attributed to the Al2(MoO4)3 phase.…”
Section: Structural Characterizations Of the Catalystsmentioning
confidence: 90%
“…After incorporation of palladium into catalysts, the Brunauer-Emmett-Teller (BET) surface area, the average pore volume, and the pore size of all catalysts were found to be smaller than the original Mo-Al catalyst. This change is obvious because of the impregnation of Pd on the support that would block the micropores of the catalysts [30]. Temperature programmed desorption (TPD) experiments of γ-Al 2 O 3 , Mo-Al and 1-4 wt% Pd/Mo-Al catalysts were performed to determine the amount and strength of acid sites.…”
Section: Physicochemical Properties Of Catalystsmentioning
confidence: 99%
“…04-0850). There is no reflection of Mo, indicating that Mo has excellent dispersion on the surface of the support . This result suggests that when Ni and Mo are jointly impregnated, a new highly dispersed (or perhaps less crystalline) structure may be formed …”
Section: Resultsmentioning
confidence: 97%
“…There is no reflection of Mo, indicating that Mo has excellent dispersion on the surface of the support. 32 This result suggests that when Ni and Mo are jointly impregnated, a new highly dispersed (or perhaps less crystalline) structure may be formed. 33 The surface morphology of the catalysts were analyzed by transmission electron microscopy (TEM) (Figure 4).…”
Section: Industrial and Engineeringmentioning
confidence: 99%